Metastable perovskite Bi1-xLaxFe0.5Sc0.5O3 phases in the range of the compositional crossover - Salak, A. N. (2019)
Perovskite ceramics of the Bi1- xLaxFe0.5Sc0.5O3 composition (0.30 ≤ x ≤ 0.35) that cannot be sintered in bulk form as a single phase using the conventional ceramic route were successfully prepared using the high-pressure/high-temperature technique. It has been shown that the room-temperature compositional crossover from the antipolar phase whose incommensurate modulation of displacements of Bi/La and oxygen is described by the Imma(00γ)s00 superspace group to the non-polar Pnma phase occurs in the narrow range between x = 0.33 and x = 0.34 with no phase coexistence. The features of this compositional crossover are discussed in comparison with that observed in the Bi1- xLaxFeO3 system.